Evaluation of an HPLC Method for Quality of Fructus of Ligustrum lucidum Ait Pieces - Luan, Lan; Xiao, Yong-Qing; Li, Li; Zhang, Cun (Asian Journal of Chemistry, 2014)
A facile and reproducible HPLC method was established for quality evaluation of fructus of Ligustrum lucidum Ait pieces, Both typical chromatograms analysis and determination analysis for main active ingredient were employed to evaluate the quality of fructus of Ligustrum lucidum Ait pieces. It is successfully applied to distinguish fructus of Ligustrum lucidum Ait from the processed products by typical chromatograms analysis and reveal the main active ingredient change rules by determination analysis. The method for typical chromatograms analysis was validated for precision, repeatability and stability, The method for determination was validated through the following performance criteria i.e., linearity, precision, repeatability, stability, accuracy, limit of detection and limit of quantification. This method is suitable for routine quantitative analysis of fructus of Ligustrum lucidum Ait before and after roasted.